Digital variance angiography allows about 70% decrease of DSA-related radiation exposure in lower limb X-ray angiography - Marcell Gyánó (Nature Portfolio, 2021)
Abstract Our aim was to investigate whether the previously observed higher contrast-to-noise ratio (CNR) and better image quality of Digital Variance Angiography (DVA) - compared to Digital Subtraction Angiography (DSA) - can be used to reduce radiation exposure in lower limb X-ray angiography. This prospective study enrolled 30 peripheral artery disease patients (mean ± SD age 70 ± 8 years) undergoing diagnostic angiography. In all patients, both normal (1.2 µGy/frame; 100%) and low-dose (0.36 µGy/frame; 30%) protocols were used for the acquisition of images in three anatomical regions (abdominal, femoral, crural). The CNR of DSA and DVA images were calculated, and the visual quality was evaluated by seven specialists using a 5-grade Likert scale. For investigating non-inferiority, the difference of low-dose DVA and normal dose DSA scores (DVA30-DSA100) was analyzed. DVA produced two- to three-fold CNR and significantly higher visual score than DSA. DVA30 proved to be superior to DSA100 in the crural region (difference 0.25 ± 0.07, p < 0.001), and there was no significant difference in the femoral (− 0.08 ± 0.06, p = 0.435) and abdominal (− 0.10 ± 0.09, p = 0.350) regions. Our data show that DVA allows about 70% reduction of DSA-related radiation exposure in lower limb X-ray angiography, providing a potential new radiation protection tool for the patients and the medical staff.